THE RELEVANCE OF THE 2013 CURRICULUM FOR PRIMARY SCHOOLS: A PSYCHOLOGICAL REVIEW - Trisnawati, Trisnawati; Dewi, Novi Ayu Kristiana; Wahyudi, Tri; Idris, Muhammad (STIT AL MULTAZAM, 2018)
Education in Indonesia several times already suffered changes curriculum and the latest curriculum is the curriculum 2013 which applied in 2013. Curriculum 2013 completion the curriculum before. One is the approach used, that is thematic integrative approach. Thematic integrative learning is intertwining learning that uses the theme to associate multiple subjects so as to provide meaningful experiences to students. This integration of material in thematic learning very appropriate with the integrative view of developmental psychology of Gestalt which refers to a sense that the whole is more meaningful than the parts. Besides the Gestalt theories, thematic integrative learning is also relevance with the theories of knowledge acquisition phase learners that’s constructivism theory which underlying of the role that experience or connections with students' learning environment.